Carboplatin and Paclitaxel in Combination With Oral Enzastaurin in Advanced Ovarian or Primary Peritoneal Cancer: Results From a Safety Lead-in Study. Issue 9 (1st November 2009) - Vergote, Ignace; Amant, Frederic; Oskay-Öezcelik, Gülten; Musib, Luna; Michel, Anne-Laure; Darstein, Christelle; Kania, Marek; Bauknecht, Thomas; Sehouli, Jalid
Abstract : Introduction: This safety lead-in study examined the pharmacokinetic and adverse event profile of combining enzastaurin with paclitaxel plus carboplatin as first-line therapy for the treatment of advanced-stage ovarian cancer and primary peritoneal carcinoma. The specific objectives of this study were to assess safety and tolerability after 2 cycles of treatment, to determine if enzastaurin alters paclitaxel and carboplatin pharmacokinetics, and to determine if enzastaurin pharmacokinetics is affected by paclitaxel and carboplatin. Methods: After debulking surgery, patients with previously untreated epithelial ovarian or primary peritoneal carcinoma received sequential paclitaxel (175 mg/m 2 ) and carboplatin (area under the curve, 5 mg × min/mL) on day 1 every 3 weeks for 6 cycles. Patients ingested an oral loading dose of 1125 mg enzastaurin on day 4 of cycle 1, followed by oral 500-mg enzastaurin daily until the end of therapy. Adverse events were graded according to the Common Terminology Criteria for Adverse Events v3.0. Results: There were 5 serious adverse events in 4 of 11 patients: soft tissue injury, wound infection, intestinal fistula, clostridial infection, and anemia. Coadministration with enzastaurin did not significantly alter paclitaxel and carboplatin pharmacokinetics (area under the curve ratio of treatment comparison ≈ 1.05 and 1.06, respectively). Enzastaurin exposures were unchanged ( C av, ss ratio of treatment comparison ≈ 0.95 for average steady-state total analyte concentrations of enzastaurin and its metabolite). Conclusions: Adding enzastaurin to paclitaxel plus carboplatin chemotherapy is feasible for advanced ovarian cancer after radical cytoreduction. Enzastaurin did not alter paclitaxel or carboplatin pharmacokinetics, and enzastaurin exposures were not significantly changed by carboplatin and paclitaxel.